Factors Affecting Preventive Behavior For Coronavirus Disease 2019 Among Village Health Volunteers Aoluk District, Krabi Province - Prakeetavatin, Suchart (Krabi Medical Journal, 2023)
The purposes of this descriptive research were to study 1) the prevention behavior of coronavirus disease 2019, 2) factors affecting the prevention behavior of coronavirus disease 2019 among village health volunteers Aoluk district, Krabi province. The sample consisted of 255 people. Data were collected using a questionnaire. The questionnaire consisted of demographical data. Knowledge test about coronavirus disease 2019 Attitude test, social support, perception in the intensity of the coronavirus disease 2019, perception in the risk related to the coronavirus disease 2019, perception in the benefit related to coronavirus 2019, perception in the barriers related to the coronavirus disease 2019, and the prevention behavior of coronavirus disease 2019, the reliability of questionnaire were more than 0.70 alpha. Data were collected using a questionnaire and then analyzed to determine frequency, percentage, mean, standard deviation, maximum value, minimum value and stepwise multiple regression analysis. The findings revealed that: 1) most of the sample groups had the prevention behavior of coronavirus disease 2019 at the highest level 89.8%. factors affecting had the prevention behavior of coronavirus disease 2019 were social support in the coronavirus disease 2019 (p-value< .001), attitude in the coronavirus disease 2019 (p-value< .001), knowledge of the coronavirus disease 2019 (p-value< .001), and perception in the coronavirus disease 2019 (p-value=.020). A social support was the greatest factor affecting the preventive behavior of coronavirus disease 2019 (β= 0.235, p-value < .001) Results of this study could be employed for determining, planning, and arranging suitable coronavirus disease 2019 preventive activities for village health volunteers during the coronavirus disease 2019 era. Activities such as organizing an online group network for providing information about severity of coronavirus disease 2019 could help increase awareness and improve preventive behaviors towards coronavirus disease 2019.